GAMBARAN POLA TERAPI OBAT PASIEN GAGAL JANTUNG DI RSUP DR. M. DJAMIL PADANG PERIODE OKTOBER-DESEMBER 2023: Description of Drug Therapy Patterns for Heart Failure Patients at RSUP Dr. M. Djamil Padang October-December 2023 period - elsa, elsa marsellinda; Aulia, Dea Suci (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2023)
ABSTRACT Heart failure is a complex clinical syndrome due to functional or structural ventricular dysfunction, resulting in symptoms of left ventricular dysfunction. The goal of treating heart failure is to reduce morbidity and mortality and prevent the worsening of heart disease. The purpose of this study was to describe the pattern of heart failure drug therapy at Dr. M.Jamil Padang Hospital. Data were collected retrospectively from the medical records of heart failure patients admitted to the cardiac ward. period October to December 2023 analyzed descriptively. Results: In this study, furosemide (31.29%) was followed by ramipril (21.09%) and candesartan (15.65%). The most common drug combination therapy was a combination of three drugs (32.14%), followed by a combination of two drugs (30.36%) and a combination of four drugs (22.32%). Conclusion: based on the results of the study, it can be concluded that the most widely used therapy is furosemide, ACEI, and ARB. The most common drug combination used for heart failure patients is ARB/ACEI and diuretics.